A rare tumor of nasal bone in a child: osteoblastoma - Kavurt, Sumru; Çorapcıoğu, Funda; Bay, Sema; Üstündağ, Emre; Akansel, Gür; Müezzinoğlu, Bahar (The Turkish Journal of Pediatrics, 2011)
Benign osteoblastoma is an uncommon bone tumor, representing 1% of all benign tumors and 3% of all primary bone tumors. Intranasal or paranasal osteoblastoma is particularly rare. Osteoblastoma occurs more frequently in males, at a peak age between 10 and 20 years. We report an osteoblastoma of the nasal septum in an 11-year-old boy who presented with swelling of the nasal septum. The diagnosis and management of this unusual lesion, as well as the histopathology and imaging characteristics, are reviewed. Magnetic resonance imaging (MRI) revealed a solid midline nasal mass originating from the septum with intense contrast enhancement. There was no evidence of osteoid or chondroid matrix mineralization on computed tomography (CT). Biopsy was performed. Histologically, the tumor contained abundant plump osteoblast-like cells, with eosinophilic cytoplasm and large nuclei that were frequently juxtaposed to the newly formed osteoid. Conservative excision was performed. The literature concerning occurrence of osteoblastoma in this unusual location is reviewed.